Corporate Social Responsibility: Development and Future - Anil Tiwari (AG Volumes, 2021)
Several nations' usage and effect of the (CSR) corporate social responsibility are examined in this study report. Many businesses are now required to portray themselves as the socially responsible in order to compete in today's competitive market. (CSR) "The Corporate Social Responsibility" has seen a rise in the academic as well as the practitioner interest, leading to the establishment of a set of concepts and its application. For each sake of such scenario, the following article analyses the general progression of concepts underlying the concept via its genesis and growth in a nation focus approach, obstacles, including literature accessible from many writers across time.